An orphaned Mce‐associated membrane protein of Mycobacterium tuberculosis is a virulence factor that stabilizes Mce transporters. Issue 1 (5th February 2016) - Perkowski, Ellen Foot; Miller, Brittany K.; McCann, Jessica R.; Sullivan, Jonathan Tabb; Malik, Seidu; Allen, Irving Coy; Godfrey, Virginia; Hayden, Jennifer D.; Braunstein, Miriam
Summary: Mycobacterium tuberculosis proteins that are exported out of the bacterial cytoplasm are ideally positioned to be virulence factors; however, the functions of individual exported proteins remain largely unknown. Previous studies identified Rv0199 as an exported membrane protein of unknown function. Here, we characterized the role of Rv0199 in M. tuberculosis virulence using an aerosol model of murine infection. Rv0199 appears to be a member of a Mce‐associated membrane (Mam) protein family leading us to rename it OmamA, for orphaned Mam protein A. Consistent with a role in Mce transport, we showed OmamA is required for cholesterol import, which is a Mce4‐dependent process. We further demonstrated a function for OmamA in stabilizing protein components of the Mce1 transporter complex. These results indicate a function of OmamA in multiple Mce transporters and one that may be analogous to the role of VirB8 in stabilizing Type IV secretion systems, as structural similarities between Mam proteins and VirB8 proteins are predicted by the Phyre 2 program. In this study, we provide functional information about OmamA and shed light on the function of Mam family proteins in Mce transporters. Abstract : Mycobacterium tuberculosis has four Mce transporters that are multiprotein complexes thought to import specific lipids. This study reveals a previously unknown role of the M. tuberculosis protein Rv0199 (OmamA) in two Mce transport systems (Mce1 and Mce4). Here we show that OmamA contributes to (i) stabilization of Mce1 transporters, (ii) Mce4 transporter function and (iii) virulence. We propose that OmamA and potentially other Mam family proteins provide structural stability to Mce transporters required for virulence.